Hydrological behaviour of vertisols in the Brazilian semi-arid region: the importance of rainfall of less than 30 mm - Andrade, Eunice; Rodrigues, Rafael; Palácio, Helba; Brasil, José; Guerreiro, Maria João (Revista Ciência Agronômica, 2020)
The greater probability of small rainfall events occurring in semi-arid regions, and the little understanding of their role in hydrological processes, has led to this investigation of surface runoff generated during these events in two adjacent micro basins in the Brazilian semi-arid region. The types of plant cover to be investigated were the Phytogeographical Caatinga Domain under regeneration for 35 years (CPDReg) and thinned CPD (CPDThin), which consisted of the elimination of trees with a diameter of